Asosiasi Kadar Fibrinogen dengan Indeks Resistensi Mikrovaskular pada Penderita Infark Miokard Akut dengan Elevasi Segmen ST yang menjalani Intervensi Koroner Perkutan Primer - Jusup Endang; Doni Firman; Iwan Dakota (Jurnal Kardiologi Indonesia, 2014)
Background: Primary percutaneus coronary intervention (PPCI) is a first of choice to return patient’s blood flow and perfusion with ST-segment elevation myocardial infarction (STEMI), however reperfusion in macrocirculation level is not always accompanied by a sufficient microcirculation reflow due to Microvascular Obstruction (MVO). Previous study demonstrated thathigh fibrinogen concentration may affect rheological parameters of the blood and play an important role in the pathomechanism of myocardial non-reperfusion phenomenon following successful mechanical recanalisation of the infarct-related coronary artery. Another study show eda more compact, lysis-resistant fibrin network in no reflow group, but without significant relation to fibrinogen level. However, there is a lack of data regarding fibrinogen and MVO. The aim of this study is to evaluate association between fibrinogen and MVO by index of microcirculatory resistance (IMR).Methods. 55 STEMI patients undergoing primary PCI were consecutively included. The fibrinogen was evaluated using clauss method and IMR was done right after PPCI to evaluate MVO.Results. From fifty-five patients included in the study, there were 87,3% men, with mean age 53,1±8.9 years old, and smoker show the biggest proportion compare with risk factor for coronary artery disease. All the patient undergo primary percutaneus coronary intervention with mean door-to-ballon time of 89.04+37.114 minute and ischemia time of 458,69+170,709 minute. Mean IMR was 55,2 + 47,454 and mean fibrinogen level was 350,8+103,19. From the scaterred plot fibrinogen prone to had a weak negative correlation with IMR and statistically non-significant(r = -0,137; p=0,319).Conclusion. There is no correlation between fibrinogen level and IMR value in STEMIpatients undergoing PPCI